Wear characteristics of flat die in flat die pellet mills based on Glycyrrhiza uralensis. (1st July 2022) - Ren, Sixue; Li, Jingbin; Shi, Yameng; Wen, Baoqin; Li, Liqiao; Su, Zipeng
Abstract: During granulation, a serious wear problem may be found in flat die as a key component of a flat die pellet mill. Specific to this problem, Glycyrrhiza uralensis was selected as the wear-causing material to investigate the wear mechanism of the flat die. Additionally, carburizing steel (20Cr and 20CrMnTi) and stainless steel (4Cr13) commonly used in flat die were adopted to conduct wear tests. To explore the influence of Glycyrrhiza uralensis powder and rods on friction and wear properties of the above three types of steel materials, a CFT-I general-purpose tester for surfaces was applied under dry friction conditions. Moreover, x-ray diffractometer (XRD), three-dimensional profilometry, scanning electron microscopy (SEM) and energy disperse spectroscopy (EDS) were used to analyze the phase compositions, surface morphologies, and elementary compositions of the samples. As demonstrated by relevant results, the influence of Glycyrrhiza uralensis on the flat die is primarily embodied in abrasive, adhesive, and fatigue wear, and a thermal oxidation reaction occurs on the surface of the flat die. By comparing the wear conditions of the three steel materials between the powder and rods of Glycyrrhiza uralensis, it is found that flat die damages caused by glycyrrhiza rods are more severe than those of its powder. Additionally, the lowest friction coefficients are generated by 20CrMnTi, which are 0.40 and 0.88, respectively. In terms of the mean wear depth, its values are 1.2 and 2 μ m, which are below those of 20Cr and 4Cr13. The results herein reveal that flat die made of 20CrMnTi have excellent wear and ductile fracture resistance characteristics. Hence, this study may provide a theoretical guide for selecting flat die materials.